THE EFFECT OF INTEGRITY, PROFESSIONALISM AND TRANSFORMATIONAL LEADERSHIP ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR IN KERINCI DISTRICT MINISTRY OF RELIGION OFFICE - Doni Mhd Hasrul; Syamsir (RADJA PUBLIKA, 2023)
Research starts from the problem of the importance of human resources as the driving force of an organization, so that organizations must encourage their employees to work more professionally and uphold integrity. However, this is not enough to require extra role behavior or behavior outside the formal role which is called Organizational Citizenship Behavior (OCB). The purpose of this research is to explain the influence of integrity, professionalism, transformational leadership and organizational citizenship behavior. This research was conducted at the Office of the Ministry of Religion, Kerinci Regency. This study uses an associative quantitative approach. The population in this study were all employees at the Office of the Ministry of Religion of Kerinci Regency, both Civil Servants (PNS) and Pramubhakti who were directly related to this research. The instrument used is a questionnaire with a Likert scale model. Data were analyzed using descriptive statistical techniques, then the analysis of the T test (partial) and the F test (simultaneous). The results showed: 1) There is an influence of integrity on OCB, 2) There is an influence of professionalism on OCB, 3) There is an influence of transformational leadership on OCB, 4) There is an influence of integrity, professionalism and overall (simultaneous) transformational leadership on OCB. Data were analyzed using descriptive statistical techniques, then the analysis of the T test (partial) and the F test (simultaneous). The results showed: 1) There is an influence of integrity on OCB, 2) There is an influence of professionalism on OCB, 3) There is an influence of transformational leadership on OCB, 4) There is an influence of integrity, professionalism and overall (simultaneous) transformational leadership on OCB. Data were analyzed using descriptive statistical techniques, then the analysis of the T test (partial) and the F test (simultaneous). The results of the study show: 1) There is an influence of integrity on OCB, 2) There is an influence of professionalism on OCB, 3) There is an influence of transformational leadership on OCB, 4) There is an influence of integrity, professionalism and overall (simultaneous) transformational leadership on OCB.